Palm-sized movable impedance detecting transducer for structural damage detection - Sun, Ke. (2009)
Non-destructive testing (NDT) in aerospace industry can make the difference between life and death. Aircraft components are inspected before they are assembled into the aircraft and then they are periodically inspected throughout their useful life. Most of the NDT methods for aerospace so far are bulky and expensive. It’s crucial to develop a method, which is portable and cheap to manufacture and use. Prof. Ling proposed a method to examine the structural integrity by using impedance transducer. Impedance transducer is a device that senses the mechanical impedance of a structure through measuring its electrical impedance. The mechanical impedance is a characteristic of structure. It is defined as the ration between the force applied to and the velocity along the force direction measured at the same given point of a structure. The mechanical impedance is independent of external force. It has been proved that by employing an impedance transducer to the surface of structure, the mechanical impedance of structure could be calculated by measuring the electrical impedance of the impedance transducer. A palm-sized movable impedance transducer is built for detecting the structural integrity of aircraft material. The impedance transducer adopts the piezoelectric ceramics to convert the mechanical impedance to electrical impedance. Aluminum alloy 6061 is made use of to simulate the aircraft skin. Three identical sized aluminum plates with different degrees of defects are used for testing the sensing ability of the self-made impedance transducer. The experiment results show that the self-made impedance transducer is able to differentiate defective structures from the healthy one by properly designing and manufacturing. It’s also sensible to the additional masses added onto the aircraft structure. In addition, the experiments prove that the impedance transducer is independent of external force, which means no matter how to place the impedance transducer, the readings would be always identical. The author successfully detected the defects on simulated aircraft structure by employing a palm-sized portable impedance transducer. The device can be further studied and utilized on real aircraft material and environment in future research.